Sol-gel derived high performance low-voltage thin film transistor - Sharma A.; Pal B.N. (My University, 2025)
Sol-gel high-k metal oxide thin film transistors (TFTs) have fascinated huge interest due to their prospective applications in cost-effective, low operating voltage electronics such as sensors, radio frequency identification tags, portable electronics and backplane circuitry for flat panel display. In this work, we report a sol-gel synthesis procedure of c-phase of lithium aluminates (c-LiAlO2) which is a high-k material due to the ionic polarization of mobile Li+ of the crystal. This high-k dielectric has been successfully utilized as a gate insulator of a low voltage indium zinc oxide (IZO) TFT. The optimize device shows a moderate on/off ratio of 9 102 and electron mobility of 4 cm2 V1 s1 under 2.0 V operation. This c- LiAlO2 dielectric has been synthesized by cost-effective sol-gel technique followed by annealing process at 700C. ©2021 Elsevier Ltd. All rights reserved.